Hysterosalpingographic findings in infertile women diagnosed with genital tuberculosis - Thangappah, Radha B. P.; Madhava, T. M. Vaishnavi; Sundaravadivelu, Pavithra; Sowparnika, Alagu S.; Ravichandran, Monika R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Objectives of the study were to describe the hysterosalpingographic (HSG) findings among infertile women with genital tuberculosis (GTB). Methods: This is a retrospective analytical study conducted at Sri Muthu Kumaran Medical College Hospital and Research Institute, Chennai, from January 2016 to January 2020. Study population included 51 infertile women with genital tuberculosis. GTB was diagnosed by either culture/histopathological examination (HPE) or polymerase chain reaction (PCR) studies. In these proved cases of tuberculosis, HSG findings were analysed. Permission from the institutional review board was obtained for the retrospective analysis of the hospital data. Results: Among 113 women who underwent hysterosalpingography, 51 were diagnosed with GTB. In these 51 women, the HSG finding were normal in 23.5% and were abnormal in 76.5% of cases. The abnormal HSG findings noted in association with GTB were calcification (3.9%) , distorted uterine cavity (3.9%), beaded tubes, intravasation with blocked tubes (5.9%), fimbrial block with hydrosalpinx (15.6%), cornual block (35.3%) and mid tubal block. Conclusions: Though imaging findings may be highly suggestive of tuberculosis, some of the features such as tubal block and hydrosalpinx are not specific for tuberculosis and may be seen in other infective causes of tubal damage also. Therefore, specific investigations for tuberculosis are still required to make a definite diagnosis. The presence of HSG features indicate that considerable tubal damage has occurred.